Super-resolution microscopy of chromatin fibers and quantitative DNA methylation analysis of DNA fiber preparations - Franek, Michal; Kilar, Agata; Fojtík, Petr; Olšinová, Marie; Benda, Aleš; Rotrekl, Vladimír; Dvořáčková, Martina; Fajkus, Jíří (Journal of cell science, 2021)
Analysis of histone variants and epigenetic marks is dominated by genome-wide approaches in the form of chromatin immunoprecipitation-sequencing (ChIP-seq) and related methods. Although uncontested in their value for single-copy genes, mapping the chromatin of DNA repeats is problematic for biochemical techniques that involve averaging of cell populations or analysis of clusters of tandem repeats in a single-cell analysis. Extending chromatin and DNA fibers allows us to study the epigenetics of individual repeats in their specific chromosomal context, and thus constitutes an important tool for gaining a complete understanding of the epigenetic organization of genomes. We report that using an optimized fiber extension protocol is essential in order to obtain more reproducible data and to minimize the clustering of fibers. We also demonstrate that the use of super-resolution microscopy is important for reliable evaluation of the distribution of histone modifications on individual fibers. Furthermore, we introduce a custom script for the analysis of methylation levels on DNA fibers and apply it to map the methylation of telomeres, ribosomal genes and centromeres.
Keywords: Chromatin; DNA Methylation; Chromatin Immunoprecipitation; DNA; mikroskopie; chromatinová imunoprecipitace; Microscopy; chromatin; metylace DNA